Spatial structuring of a Legionella pneumophila population within the water system of a large occupational building. Issue 10 (12th October 2018) - David, Sophia; Mentasti, Massimo; Lai, Sandra; Vaghji, Lalita; Ready, Derren; Chalker, Victoria J.; Parkhill, Julian
Abstract : The diversity of Legionella pneumophila populations within single water systems is not well understood, particularly in those unassociated with cases of Legionnaires' disease. Here, we performed genomic analysis of 235 L. pneumophila isolates obtained from 28 water samples in 13 locations within a large occupational building. Despite regular treatment, the water system of this building is thought to have been colonized by L. pneumophila for at least 30 years without evidence of association with Legionnaires' disease cases. All isolates belonged to one of three sequence types (STs), ST27 ( n =81), ST68 ( n =122) and ST87 ( n =32), all three of which have been recovered from Legionnaires' disease patients previously. Pairwise single nucleotide polymorphism differences amongst isolates of the same ST were low, ranging from 0 to 19 in ST27, from 0 to 30 in ST68 and from 0 to 7 in ST87, and no homologous recombination was observed in any lineage. However, there was evidence of horizontal transfer of a plasmid, which was found in all ST87 isolates and only one ST68 isolate. A single ST was found in 10/13 sampled locations, and isolates of each ST were also more similar to those from the same location compared with those from different locations, demonstrating spatial structuring of the population within the water system. These findings provide the first insights into the diversity and genomic evolution of a L. pneumophila population within a complex water system not associated with disease.